2020
DOI: 10.1186/s12954-020-00448-2
|View full text |Cite
|
Sign up to set email alerts
|

New psychoactive substances in Eurasia: a qualitative study of people who use drugs and harm reduction services in six countries

Abstract: Background This study examines the use of new psychoactive substances (NPS) and the harm reduction response in six Eurasian countries: Belarus, Moldova, Serbia, Kazakhstan, Kyrgyzstan, and Georgia. The aim is to identify current patterns of NPS use and related harms in each country through recording the perspectives and lived experience of people who use drugs and people who provide harm reduction services in order to inform the harm reduction response. Methodology The study involved desk-based research and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…A study by Elliott et al showed that marijuana and SCs are not commonly used interchangeably by the same individuals, implying either that the substance effects are sufficiently different, or that SCs are used out of a perceived necessity, not preference ( 40 ). In Serbia, NPS were commonly consumed in combination with amphetamines, cocaine, ecstasy, alcohol and cannabis ( 11 ). Reasons for drug combinations were: to prolong or amplify the drug’s effects, to add a new effect and to alleviate drug hangovers ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Elliott et al showed that marijuana and SCs are not commonly used interchangeably by the same individuals, implying either that the substance effects are sufficiently different, or that SCs are used out of a perceived necessity, not preference ( 40 ). In Serbia, NPS were commonly consumed in combination with amphetamines, cocaine, ecstasy, alcohol and cannabis ( 11 ). Reasons for drug combinations were: to prolong or amplify the drug’s effects, to add a new effect and to alleviate drug hangovers ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia, NPS were commonly consumed in combination with amphetamines, cocaine, ecstasy, alcohol and cannabis ( 11 ). Reasons for drug combinations were: to prolong or amplify the drug’s effects, to add a new effect and to alleviate drug hangovers ( 11 ). Acute side effects reported strongly support those described in the literature and included dry mouth, trouble thinking clearly, panic attack, palpitations and fear ( 6 , 11 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] Authors describe the use of drugs with clients as a social aspect of their occupation, 51 while improving their performance. 52 Further, some argue that this is a difficult aspect to avoid with clients who are regular drug users. 49 Another interlinked factor was feeling sexually attracted to clients that implied opting for personal pleasure over a professional perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, just two reliable publications in international peer-reviewed journals are available regarding NPSs in Serbia. The first one pointed out clinical and analytical experience of the Serbian National Poison Control Centre with synthetic cannabinoids [ 8 ], while the second one examined the use of NPSs in light of harm-reduction responses in six Euroasian countries, including Serbia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%